Aspects of the Surgical Management of Acute Biliary Pancreatitis - Khamroev, O.Z.; Dusiyarov, M.M.; Khuzhabaev, S.T.; Saidov, M.S.; Ruzimurodov, N.F. (Journal of Neonatal Surgery, 2025)
This study presents a retrospective analysis of the management of 221 patients with acute biliary pancreatitis. In cases of gallstone impaction in the major duodenal papilla, endoscopic papillotomy is recommended within the first few hours; in patients with choledocholithiasis, obstructive jaundice, cholangitis, and acute biliary pancreatitis, endoscopic papillotomy combined with lithoextraction should be performed within the first 24 hours of hospital admission. Cholecystectomy—preferably performed laparoscopically—is indicated after conservative resolution of mild biliary pancreatitis, optimally within 3–7 days. When endoscopic papillotomy is uneventful, cholecystectomy may also be performed during the same hospitalization without prior discharge. In cases of acute biliary pancreatitis complicated by sterile or infected fluid collections, cholecystectomy should be deferred until complete resolution of these collections and the abatement of the systemic inflammatory response